Adjectives as a Persuasive Strategy in Online Book Reviews - Heřmánková, Eliška (Univerzita Pardubice, 2022)
The focus of this bachelor thesis is to analyze the use of adjectives as a persuasive strategy in online book reviews. The theoretical part concerns with book review as a genre, its structure and evaluative language, and also describes adjectives, their morphology, syntax, and semantics. The practical part consists of methodology and framework used to analyze the corpus of this thesis and also presents findings and results of the analysis.
Adjektiva jako přesvědčovací strategie v online recenzích knih
Keywords: knižní recenze; hodnotící jazyk; adjektivum; morfologie adjektiv; syntax adjektiv; sémantika adjektiv; book review; evaluative language; adjective; morphology of adjectives; syntax of adjectives; semantics of adjectives